ECONOMIC GROWTH AND TAXATION IN CENTRAL AND EASTERN EUROPE - Cristina BOROVINA (COJOCARU) (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
In the context of the economic crisis that started in the United States in 2007, economic growth has become of great importance for the countries affected by the crisis further to their confrontation with lower growth rates of GDP per capita. At national level, governments are searching for that mix of optimal economic policies that would revive economies on the upward and also sustainable trend. One of the key policies in this regard, especially for the countries in Central and Eastern Europe which intend to adopt the euro currency, is the tax policy. Its main instruments are taxes. In this paper, we pay special attention to these instruments and to the connection that they have with the economic growth. This paper is divided into three parts. The first part presents a few ideas related to the importance of taxes at national level, the second part is an analysis in terms of taxation of the Central and Eastern Europe countries, while the third part consists of a panel-type assessment of the relation between economic growth and taxation level.